2017
DOI: 10.1039/c6sc04788b
|View full text |Cite
|
Sign up to set email alerts
|

Why conclusions from platinum model surfaces do not necessarily lead to enhanced nanoparticle catalysts for the oxygen reduction reaction

Abstract: Platinum model-surface and nanoparticle catalysts for the oxygen reduction reaction are enhanced by the presence of concave sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
235
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(249 citation statements)
references
References 52 publications
12
235
0
2
Order By: Relevance
“…To bridge the gap between the adsorption-energy-based prediction and real performance of catalysts, several attempts have been made to combine structural factors and adsorption energies as a descriptor of OER efficiency, although further studies are needed for verification and extensive application of these approaches. [198,199] Electronic structure parameters can be more intuitive descriptors than adsorption energies because they govern the adsorption energies. However, the large structural differences between metal oxide material groups limit the identification of electronic-structure-based descriptors that can be generally applied to all metal oxides.…”
Section: Definition Of Descriptor For Rational Design Of Catalystsmentioning
confidence: 99%
“…To bridge the gap between the adsorption-energy-based prediction and real performance of catalysts, several attempts have been made to combine structural factors and adsorption energies as a descriptor of OER efficiency, although further studies are needed for verification and extensive application of these approaches. [198,199] Electronic structure parameters can be more intuitive descriptors than adsorption energies because they govern the adsorption energies. However, the large structural differences between metal oxide material groups limit the identification of electronic-structure-based descriptors that can be generally applied to all metal oxides.…”
Section: Definition Of Descriptor For Rational Design Of Catalystsmentioning
confidence: 99%
“…[10,11] Further details about the GCN are provided in the Supporting Information. [12][13][14] Recently,t he concept of GCN was further extended to predict the ORR mass activities in absolute units of Amg Pt À1 for nanostructured Pt electrocatalysts of various sizes. [11] Experimental ORR activity measurements on model Pt singlecrystalline surfaces confirmed that indeed, GCN can be used as ad escriptor for catalytic performance towards the ORR.…”
mentioning
confidence: 99%
“…Meanwhile, the R NiNi of the PtNi/C electrocatalyst throughout the whole potential cycles remains nearly unchanged, and perfectly matches the R NiNi (2.572 Å) derived from Vegard's law based on the Ni relative content in the PtNi 3 precursor (75%) (Figure 6). The combination of the trends of R PtPt and R NiNi with potential cycling depicts that the core of the PtNi/C carries the PtNi 3 phase from the PtNi 3 precursor and remains intact during long-term PEMFC operation, whereas the 1,2,3 weighting at Pt L 3 and Ni k edges simultaneously. For Pt, 1.1< R < 3.4 Å and k = 2.95 − 12.14 Å −1 were used; for Ni, 1.2 < R < 3.0 Å and k = 1.87 -11.93 Å −1 were used.…”
Section: Resultsmentioning
confidence: 99%
“…The ORR activity of platinum can be significantly improved by alloying Pt with a wide range of transition metals (denoted as M) such as Co, Ni, Y, and the activity improvement has been attributed to the strain and/or ligand effects induced by M via optimization of the Pt-O binding energy and surface coordinate configuration. [1][2][3][4][5] However, the activity gain induced by M is generally not sustainable owing primarily to the dissolution of M during long-term PEMFC operation, which leads to the attenuation of strain/ligand effects, particle growth, and the loss of the favorable surface coordinate configuration. 6 Huang et al 7 recently reported that both the activity and durability of the PtNi/C octahedral NPs can be markedly improved by doping with a transition metal such as Mo on the surface.…”
mentioning
confidence: 99%